Electrochemical Studies of Bismuth(III) Complexes by Polarographic Technique - Kumar, Santosh; Gupta, O.D. (Asian Journal of Chemistry, 2010)
Polarograhic studies of Bi(III) complexes with L-tyrosine, citrulline, citraconic acid and hippuric acid have been studied at two different temperatures using potassium nitrate as supporting electrolyte in aqueous medium. In all the systems, Bi(III) reduced quasireversibly with the involvement of three electrons. The overall formation constants were determined by DeFord and Hume's method. There was no change in the numbers of species formed by increasing the temperature from 300-308 K but the stability constants of complex species decreased with the rise in temperature. It was found that stability constants of Bi(III)-L-tyrosinate system was highest in comparison to other systems.